A drosomycin-GFP reporter transgene reveals a local immune response in Drosophila that is not dependent on the Toll pathway. - Ferrandon, D.; Jung, A.C.; Criqui, M.; Lemaitre, B.; Uttenweiler-Joseph, S.; Michaut, L.; Reichhart, J.; Hoffmann, J.A. (The EMBO Journal, 1998)
A hallmark of the systemic antimicrobial response of Drosophila is the synthesis by the fat body of several antimicrobial peptides which are released into the hemolymph in response to a septic injury. One of these peptides, drosomycin, is active primarily against fungi. Using a drosomycin-green fluorescent protein (GFP) reporter gene, we now show that in addition to the fat body, a variety of epithelial tissues that are in direct contact with the external environment, including those of the respiratory, digestive and reproductive tracts, can express the antifungal peptide, suggesting a local response to infections affecting these barrier tissues. As is the case for vertebrate epithelia, insect epithelia appear to be more than passive physical barriers and are likely to constitute an active component of innate immunity. We also show that, in contrast to the systemic antifungal response, this local immune response is independent of the Toll pathway.